Plasma-activated water for disinfection and quality retention of sea bream fillets: Kinetic evaluation and process optimization. (May 2023) - Chanioti, Sofia; Giannoglou, Marianna; Stergiou, Panagiota; Passaras, Dimitrios; Dimitrakellis, Panagiotis; Kokkoris, George; Gogolides, Evangelos; Katsaros, George
Abstract: The efficacy of plasma-activated water (PAW) in the decontamination of sea bream fillets at various processing conditions including fish/immersion agent ratio (1/1–1/5) and immersion times (0–20 min), was evaluated. Deionized water (as control samples) and artificially produced water (artificial) with equal reactive species (H2 O2, NO2 −, and NO3 − ) concentrations to PAW were also used as immersion agents for comparison purposes. All the fillets were assessed in terms of their microbiological (total aerobic bacteria – TAB, yeasts/molds, hydrogen sulfide (H2 S)-producing microorganisms, lactic acid bacteria – LAB, Pseudomonas spp., Brochotrix thermosphacta, and Enterobacteriaceae ) and physicochemical (color, texture, lipid oxidation) characteristics. PAW-treated samples exhibited the highest microbial reduction; the loads of TAB, Pseudomonas spp., yeasts/molds, Enterobacteriaceae, H2 S-producing bacteria and Brochotrix thermosphacta were reduced by approximately 1.58, 2.25, 3.95, 2.14, 1.96 and 1.48 logCFU/g, respectively compared to the fish initial natural microbiota (6.81, 6.25, 3.95, 5.14, 4.96 and 4.81 logCFU/g, respectively) at the most intense process conditions (fish/immersion agent ratio of 1/5 and immersion time of 20 min) ( p  < 0.05). Shelf-life study of all treated fillets was conducted to validate the efficiency of PAW. During 10-d storage at 4 °C, the PAW-processed sea bream fillets had lower microbial growth rates (i.e. for TAB growth, the rate was 0.440 d −1 for PAW-treated compared to 0.640 d −1 for untreated fillets) and retained their color and hardness, while total volatile basic nitrogen (TVB-N) remained at low levels (14.90 mg N/100 g) compared to the untreated ones (21.84 mg N/100 g). Their shelf-life was extended by approximately 60% and 30% for PAW- and artificially processed samples, respectively, (2.8- and 1.4-day shelf-life extension compared to control samples, respectively). These aforementioned data show that PAW can be efficiently used as a disinfectant agent to control microbial degradation, while retaining the quality of fish fillets. Industrial relevance: Fish fillets are perishable food products, while none of the conventional or novel processing technologies or techniques may be applied for initial microbial population decrease. Storage and transportation at refrigeration temperatures below 1 °C (within Styrofoam insulated boxes full of ice flakes) is the target of the relevant companies for extending the shelf-life as much as possible. An alternative approach for reducing the initial microbial load and the microbial growth rate of fish fillets during storage and transportation is proposed, by immersing the fillets into Plasma activated water with antimicrobial properties. The microbial load is significantly reduced, resulting in a shelf-life extension by at least 60%. This allows for more distant transportation of the fillets and for less food waste since there is more time for consumption before spoilage. Highlights: The shelf-life of sea bream fillets stored at 4 °C was extended after 20 min treatment with plasma activated water (PAW) No alteration of quality indices (color and texture) was observed when PAW treatment was applied Slight increase of oxidation was observed, but within the acceptability limits